Pengaruh Model Pembelajaran Kooperatif Teams Games Tournament (TGT) Terhadap Penguasaan Maharotul Kitabah di Kelas VII SMP Ma’arif 01 Nurul Muttaqin Tlogowaru Malang - Rohmah, Ika Jami'atur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study examines the influence of the Teams Games Tournament (TGT) cooperative learning model on students' mastery of the Maharotul Kitabah. The purpose of this study was to determine the extent of the influence and effectiveness of the Teams Games Tournament (TGT) cooperative learning model on the mastery of the Maharotul Kitabah in grade VII students at SMP Ma'arif 01 Nurul Muttaqin Tlogowaru Malang. A non-experimental quantitative method with a descriptive type was used in this study. Because the sample size chosen to represent the population as a whole, consisting of 49 respondents, with a 5% error table, this study used sample probability. However, for data analysis, a simple linear regression formula, instrument validity and reliability tests, classical assumption tests, and hypothesis tests were used. The results of this study are the mastery of maharotul kitabah in SMP Ma'arif 01 Nurul Muttaqin Tlogowaru Malang is influenced by the cooperative learning model of teams games tournament significantly seen from the results of the test that has been carried out with the value of the t-test H1, namely (10.193> 2.012) which means the working hypothesis is accepted. The cooperative learning model of teams games tournament is also effective in mastering maharotul kitabah in SMP Ma'arif 01 Nurul Muttaqin Tlogowaru Malang supported by the R2 figure of 68.9% which means it has a high influence.